Experimental Investigation on Spirogyra Biodiesel With Di‐Tert‐Butyl Peroxide as a Cetane Booster - Aravind Samraj; Debabrata Barik; Kapura Tudu; Prabhu Paramasivam; Praveen Kumar Kanti; Abinet G. Ayanie (Energy Science & Engineering)
ABSTRACT This study investigates the impact of incorporating 30% spirogyra algae biodiesel (SBD30) with di‐tert butyl peroxide (DTBP) as a cetane booster on combustion, performance, and emissions in a diesel engine. The investigators tested diesel blends which included SBD30 + 1%DTBP, SBD30 + 1.5%DTBP, and SBD30 + 2%DTBP. Analysis revealed that DTBP addition shortens the ignition delay period thus improving combustion efficiency. The ignition delay reached 9.43°CA aTDC with the SBD30 + 2%DTBP blend at full load although SBD30 stood at 10.26°CA aTDC and diesel delivered 11.5°CA aTDC. The combustion duration (CD) increased while SBD30 + 1.5%DTBP achieved a maximum combustion pressure (MCP) level that matched almost perfectly with SBD30 + 2%DTBP. The brake thermal efficiency (BTE) of DTBP blends was rated at 6.06% lower than diesel fuel and reached 10.41% lower at its utmost level. The emissions analysis displayed significant CO reduction by 53.8%, as well as decreased HC levels but NO levels grew by 9.1% to reach 24.9%. The smoke emission levels decreased significantly as SBD30 + 1.5%DTBP produced 28.8% less smoke emissions compared to diesel port fuel. Research indicates that additions of DTBP to SBD30 produce more favorable combustion and emission performance thus establishing potential as an attractive diesel fuel choice.